An Intravenous Bolus of Epa: Dha 6. Issue 5 (November 2016) - Burban, Mélanie; Meyer, Grégory; Olland, Anne; Séverac, François; Yver, Blandine; Toti, Florence; Schini-Kerth, Valérie; Meziani, Ferhat; Boisramé-Helms, Julie
ABSTRACT: Introduction: Enriching the diet with Omega-3 for several weeks improves myocardial resistance to ischemia-reperfusion (IR) in rats. However, patients with myocardial infarction requiring an emergency reperfusion cannot be pretreated with such a diet. The objective of our study was to describe the effects of an intravenous Omega-3 bolus before reperfusion in a rat model of myocardial IR. Methods: In a rat model of acute myocardial IR, an intravenous Omega-3 bolus (EPA:DHA 6:1), associated or not with iodinated contrast media, was administered after a 30-min ischemia, before reperfusion. Hemodynamic parameters were assessed. Circulating procoagulant microparticles were phenotyped. Vascular and heart inflammation, superoxide anion, and nitric oxide were measured. Ex vivo vascular reactivity was performed with a pharmacological selective inhibitor of inductible nitric oxide synthase. Cardiac troponin I (cTn-I) plasma levels were measured. Results: Compared with untreated IR rats, an Omega-3 bolus before reperfusion significantly decreased the IR syndrome, improving mean arterial pressure (114 ± 9 vs. 61 ± 17 mmHg 4 h after reperfusion, P  < 0.05) and carotid blood flow, and decreasing plasma cTn-I levels after revascularization. These beneficial effects may be due to improved ex vivo mesenteric resistance artery sensitivity to phenylephrine, endothelial protection assessed by decreased endothelial CD54 + microparticle release (9.1 ± 2.5 vs. 4.8 ± 2.0 nM Eq PhtdSer, P  < 0.05) and reduced vascular inflammation and oxidative stress. Conclusions: In this rat model of myocardial IR, an intravenous Omega-3 bolus before reperfusion decreases IR-induced vascular failure and shock. These results open therapeutic perspectives as far as myocardial reperfusion process is concerned that deserve further explorations in humans.